Efficiency of gas pipeline distribution systems - Тамаргазін, О.А.; Науменко, Н.Г. (Proceedings of National Aviation University, 2008)
Considered to the methods of increasing of the effectiveness of aggregated tube transport distributing systems with stochastic continuous consumption of desired product functioning.